2006
DOI: 10.1177/1527154406296481
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Urban and Rural Nursing Workforce Shortages in Nebraska Hospitals

Abstract: Current workforce models that rely on economic indicators have seriously underestimated the rural RN shortage and its impact on rural hospitals. This cross-sectional study developed an algorithm using the concept of need and applied it to health service demand data in 66 counties of a midwestern state (1993-2002) to determine trends in RN shortages between urban and rural areas. Results showed that rural areas consistently had the largest gap between predicted need for RNs and numbers employed and that the rur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…For example, Cramer et al (2006), who estimate urban and rural county-level nursing shortages, compute shortages based on comparisons of the "actual number of RNs employed in hospital-based settings with targets of RN need", where RN needs are estimated based on "the amount of labor thought necessary to deliver safe, effective, or 41 Suppose that the hospital were required, by state law, to hire a minimum number of nurses. If this legally-mandated minimum were between points H and F, the hospital with budget B 1 would be out of compliance with the law and potentially subject to some fine.…”
Section: "Professional Standards" Shortagesmentioning
confidence: 99%
“…For example, Cramer et al (2006), who estimate urban and rural county-level nursing shortages, compute shortages based on comparisons of the "actual number of RNs employed in hospital-based settings with targets of RN need", where RN needs are estimated based on "the amount of labor thought necessary to deliver safe, effective, or 41 Suppose that the hospital were required, by state law, to hire a minimum number of nurses. If this legally-mandated minimum were between points H and F, the hospital with budget B 1 would be out of compliance with the law and potentially subject to some fine.…”
Section: "Professional Standards" Shortagesmentioning
confidence: 99%
“…A broad perspective that includes all health professions is required when addressing the rural health workforce, with the ultimate goal of promoting the health of the population. Currently, criteria to define health professional shortage areas generally only address the supply of primary care physicians, dentists, and mental health professionals, overlooking the potential influence of nurses and other rural health care providers including pharmacists and physician assistants . This study suggests this policy gap may contribute to missed opportunities to optimize workforce distribution to meet community needs.…”
Section: Discussionmentioning
confidence: 95%
“…Maintaining an adequate health care workforce constitutes one of the most serious and persistent challenges facing rural health care today. This problem is well documented in relation to shortages and maldistribution issues in most health care professions, including nursing, medicine, and dentistry . Knapp and Hardwick examined national ZIP code‐level data and found the national primary care physician‐to‐population ratio per 100,000 population to be 178% of the rural ratio (95.2 nationally; 53.6 rural) and 138% for dentists (75.9 nationally; 55.0 rural) .…”
mentioning
confidence: 99%
“…A sufficient number of nursing personnel is a crucial factor for the level of work stress that nurses experience; particularly in rural areas where a shortage of nurses has been a perpetual problem. Moreover, the lack of nursing staff and job dissatisfaction are the primary reasons forcing nurses to resign (Cramer, Nienaber, & Helget, 2006). In a previous study focusing on participants with nursing as their first job, the results showed that 37% of the participants resigned within the first year, and 57% resigned within 2 years.…”
Section: Associated Factors Of Work Stress For the 2 Areasmentioning
confidence: 99%